Human Dental Pulp Stem Cells: The Culture Optimization for Increased Growth - MR Baghaban Eslaminejad; H Nazarian; M Shariati; S Vahabi (International Journal of Hematology-Oncology and Stem Cell Research, 2009)
Introduction: Dental pulp-derived mesenchymal stem cells (MSCs) have emerged as a promising tool for use in regenerative medicine. The in vitro growth kinetic and culture requirement of the cells derived from human dental pulp, which is the subject of this present study, is poorly described. Materials and Methods: Stem cells were derived from human third molar and then characterized. The in vitro growth kinetics of the cells was examined by colonogenic assay and a determination of the population doubling number (PDN). Finally, the culture conditions were optimized for pulp stem cell maximum proliferation. Results: Propagated dental pulp cells tended to differentiate into odontoblast, osteoblast, adipose and cartilage cells. Typically surface antigens were expressed as mesenchymal stem cells. The cells tended to be very proliferative with a PDN value of about 11. The colonogenic efficiency was about 60% and an average colony size was about 10.75±1.58 mm2. The best culture condition for enhanced proliferation was achieved when the cells were seeded at 100 cells/cm2 in a the presence of 20% FBS in a medium (P<0.05). Conclusion: Taken together, the optimal culture conditions for human dental pulp-derived MSCs were determined. This information is helpful with respect to cell in vitro propagation which is greatly needed prior to their transplantation.